RETRACTED ARTICLE: Belinostat suppresses cell proliferation by inactivating Wnt/β-catenin pathway and promotes apoptosis through regulating PKC pathway in breast cancer. Issue 1 (4th December 2019) - Lu, Pengwei; Gu, Yuanting; Li, Lin; Wang, Fang; Yang, Xue; Yang, Yunqing
Abstract : We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article: Pengwei Lu, Yuanting Gu, Lin Li, Fang Wang, Xue Yang & Yunqing Yang (2019) Belinostat suppresses cell proliferation by inactivating Wnt/β-catenin pathway and promotes apoptosis through regulating PKC pathway in breast cancer. Artificial Cells, Nanomedicine, and Biotechnology, 47(1), 3955–3960, DOI: 10.1080/21691401.2019.1671855 Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors checked their data and confirmed there are fundamental errors present. Therefore, they have agreed to the retraction of this article. The authors apologise for this oversight. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.